Wide-Area H∞ Control for Damping Interarea Oscillations with Event-Triggered Scheme. (30th May 2013) - Zhang, Yunning; Yue, Dong; Hu, Songlin
Abstract : An event-triggered scheme is adopted and applied to the design of a centralized wide-area H ∞ damping controller (WAHDC) of interconnected power systems with external disturbance. Firstly, based on the linearized multimachine system model, the centralized WAHDC with event-triggered scheme design problem is described as time-delay feedback control problem. Then by using Lyapunov functional method and Jensen inequality technique, criteria for stability with an H ∞ norm bound and for design of the feedback controller are derived. The linear matrix inequality (LMI) is employed to solve the feedback gain. Finally, case studies are carried out based on two-area four-machine power system. Simulations indicate that the proposed WAHDC with event-triggered scheme can damp the interarea oscillation effectively when the external disturbance is bounded and significantly reduce the number of measured states released to WAHDC. Relationships between event trigger parameter σ and dynamic performance, σ and network utilization, σ and time delay, and σ and disturbance rejection level are investigated and results obtained can be used to choose an appropriate event trigger parameter.